Navigation in Contour-Drawn Scenes Using Augmented Reality. (January 2022) - Sawada, Tadamasa; Mendoza Arvizu, Alejandro; Farshchi, Maddex; Kiba, Alexandra
The visual system can recover 3D information from many different types of visual information, e.g., contour-drawings. How well can people navigate in a real dynamic environment with contour-drawings? This question was addressed by developing an AR-device that could show a contour-drawing of a real scene in an immersive manner and by conducting an observational field study in which the two authors navigated in real environments wearing this AR-device. The navigation with contour-drawings was difficult in natural scenes but easy in urban scenes. This suggests that the visual information from natural and urban environments is sufficiently different and our visual system can accommodate to this difference of the visual information in different environments.